Polyamines in intestinal and pancreatic adaptation. (1987) - Luk, G D; Yang, P
Abstract : The intestinal mucosa is a rapidly proliferative tissue, with a highly dynamic cell population. Its total cellular mass is well controlled and can adapt, with hypo- or hyperplasia, to a wide variety of stimuli. Luminal nutrients, hormonal factors, and pancreatic and biliary secretions have all been implicated in the regulation of intestinal mucosal adaptation. Similarly, the same factors appear essential for the maintenance of exocrine pancreatic structure and function. The polyamines (putrescine, spermidine, and spermine) and the key enzyme controlling their synthesis (ornithine decarboxylase, ODC) are important for many cell growth processes, and may play important roles in intestinal and pancreatic adaptation. During intestinal adaptation in response to jejunectomy, lactation and pancreatico-biliary diversion (PBD), intestinal contents of ODC and polyamines are increased, paralleling increases in mucosal proliferative indices and DNA synthesis. With administration of the specific inhibitor of ODC (difluoromethylornithine, DFMO) the increases in ODC and polyamines are suppressed, and intestinal adaptation is abrogated. In pancreatic hyperplasia induced by caerulein, pancreatic polyamines are increased. With DFMO administration, caerulein-induced increases in pancreatic DNA synthesis were inhibited and pancreatic hypertrophy was partially suppressed. PBD-induced pancreatic hypertrophy, however, was not affected by DFMO. Thus, the role of polyamines in the adaptation of the pancreas, with a relatively quiescent proliferative status, is as yet undefined. It seems clear, however, that the induction of ODC and the resultant increase in polyamine biosynthesis are critical for the normal growth and especially for adaptive hyperplasia of the intestinal mucosa.